Hybrids and Contradictions : Human Resource Management in the Contemporary Public Sector - Colley, Linda; McCourt, Willy; Waterhouse, Jennifer (Taylor and Francis, 2013)
Public employment is a dynamic field of study, buffeted by the ever-changing and reforming public sector environment and by external events such as changing demographics and the global financial crisis. This first article to the special edition on contemporary public sector human resources provides a broad overview of recent developments, starting with the nature of public sector reforms and proceeding with analysis of the far-reaching effects on public employment. For many western countries, this has led to a hybrid model of old and new practices, with many internal contradictions and a confusing array of accountabilities. The new arrangements led to a de-privileging of public servants through reductions in merit and tenure. They also reduced the institutional capacity of central personnel institutions to co-ordinate and monitor public employment and public management. The article proceeds with a review of the implications of these changes in the face of new challenges such as skills shortages and economic pressures. This overview provides a backdrop for the variety of articles presented in the special edition.